The Interaction of Green Banking Initiative, ESG Disclosure, and Environmental Performance on Net Income of the Strongest Banks in Asia - Andika Rendra Bimantara; Ely Windarti Hastuti; Hartomi Maulana; Fahmilia Rahmanita (INSTITUT AGAMA ISLAM SEBI, 2025)
Today's environmental issues require quick and precise handling. Although it is not the leading actor of natural damage, the banking sector must still practice sustainable development without releasing its function as a profit institution. This study uses a quantitative method with content analysis on the annual report and the Sustainability Report of 10 Islamic banks, which were sampled using purposive sampling as the sampling technique—data analysis techniques using panel data analysis. The results of the study are partially mixed results. Green Banking and environmental performance variables each negatively affect the Net Income variable, with each t value lower than the t table value and a significance value greater than 0.05. In contrast, the effect between the ESG Disclosure variable and the Net Income variable is positive and significant. This results is similar to the simultaneous test results. Simultaneously, the Green Banking, ESG Disclosure, and Environmental Performance variables have a positive and significant effect on the Net Income variable. It can be concluded that if Islamic Banking wants to achieve an optimal level of profitability while in line with sustainable development practices, then Islamic Banking can strive for these three elements simultaneously. That is, carrying out Green Banking practices, disclosing ESG practices, and maximizing environmental performance. Isu lingkungan hidup di masa kini membutuhkan penanganan-penanganan yang cepat dan tepat. Meskipun bukan sebagai aktor utama kerusakan alam, sektor Perbankan tetap harus mempraktikkan Pembangunan berkelanjutan tanpa melepaskan fungsinya sebagai lembaga profit. Penelitian ini menggunakan metode kuantitatif dengan analisis konten pada laporan tahunan dan Sustainability Report sejumlah 10 bank Islam yang menjadi sampel dengan purposive sampling sebagai Teknik sampelnya. Teknik analisis data menggunakan panel data analysis. Hasil penelitian dapat disimpulkan bahwa secara parsial terdapat hasil yang beragam. Variabel Green Banking dan performa lingkungan masing-masing berpengaruh negatif terhadap variabel Net Income dengan masing-masing nilai t hitung lebih rendah dari nilai t tabel serta nilai signifikansi yang lebih besar dari 0.05. Berbeda halnya dengan pengaruh antara variabel Pengungkapan ESG terhadap variabel Net Income yang berpengaruh positif dan signifikan. Hasil ini serupa dengan hasil uji secara simultan. Secara simultan, variabel Green Banking, Pengungkapan ESG, dan Performa Lingkungan berpengaruh positif dan signifikan terhadap variabel Net Income. Sehingga dapat disimpulkan jika Perbankan Islam hendak mencapai Tingkat profitabilitas yang optimal sekaligus sejalan dengan praktik Pembangunan berkelanjutan, maka Perbankan Islam dapat mengupayakan ketiga elemen ini secara bersamaan. Yaitu menjalankan praktik Green Banking, mengungkapkan praktik ESG, serta memaksimalkan performa lingkungannya